Development and Validation of Method for the Quantitative Determination of Zinc in its Chelate Complexes Using Energy Dispersive X-ray Fluorescence Spectroscopy - А. V. Marukhlenko; Т. V. Maksimova; Т. V. Pleteneva; М. A. Morozova (Разработка и регистрация лекарственных средств)
Introduction. The production, standardization and quality control process of various dietary supplements containing chelated zinc requires validated quantitative assessment methods. In this work, we propose an X-ray fluorescence spectroscopy (XRF) technique for determining the zinc content in the composition of coordination compounds using the example of a synthesized chelate complex with methionine.Aim. To synthesize Zn(Met)2 chelate complex, to develop and validate a method for its quantitative analysis using the XRF method.Materials and methods. The synthesized zinc chelate complex was investigated by IR spectroscopy. The XRF method was used to develop a method for quantifying the zinc content in the synthesized complex. We used dry mixtures of zinc sulfate monohydrate and L-methionine (Met) in a molar ratio of Zn to Met – 1 : 1, 1 : 2, 1 : 4, 1 : 8 and 1 : 16 and also aqueous solutions of zinc sulfate and L-methionine in a molar ratio of Zn to Met 1 : 2 with Zn concentrations from 0.5 to 100 mmol/l as calibration standards. Complexometric titration was used as an arbitration method for the quantitative determination of zinc content in the samples under study.Results and discussion. The IR spectrum of chelate complex confirmed the presence of a donor-acceptor bond between Zn2+ and the nitrogen atom of amino group in methionine. The titration results showed chelate compounds have a composition corresponding to the stoichiometric formula Zn(Met)2. XRF analysis of dry standard mixed samples demonstrated the presence of matrix effect, that makes impossible an accurate assessment of zinc content in the chelate compound. According to the XRF spectra of aqueous solutions containing zinc sulfate and methionine in a ratio of 1 : 2 at a zinc concentration of 0.5; 1; 2; 3; 4; 5; 10; 25; 50 and 100 mmol/L, a calibration graph was constructed – the dependence of the fluorescence signal intensity for the Kα line of zinc on the concentration of zinc in the solution (r = 0.9996). The method was evaluated by the following validation parameters: specificity, linearity, correctness, precision, and analytical range. The specificity of the validated method was proven in the presence of copper, iron, and silver.Conclusion. The developed method make it possible to determine with sufficient precision and correctness the content of Zn2+ in its aqueous solutions of inorganic and organic nature by the XRF method in the concentration range from 3 to 100 mmol/l without the influence of the matrix.